MADRASAH: BASIS EPISTEMOLOGI HUMANISTIK-RELIGIUS - Aprison, Wedra (Program Studi Pendidikan Agama Islam, 2017)
MADRASAH: THE BASIS OF HUMANISTIC-RELIGIOUS EPISTEMOLOGY. In anthropocentrism modernity, which is often called humanism, it is assumed that life is not centered on God or gods, but in humans. This western epistemology has been criticized by the westerners themselves. Nietzshe and Capra stated that Western civilization has been destroyed due to overly laud the ratio. The purpose of the research is to find the solution of the modern human’s problem. The research method used is library method and analyzed by philoshophy approach. The result shows that madrasah is the way out of the humanity problems. It means that madrasah education system could be a solution to the crisis of modern human. The madrasah epitemology is humanistic-religious. From the design model, madrasah is better than public schools since the general knowledge given in madrasah is totally the same as in public schools, the advantage lies in the Islamic system. Madrasah graduates are expected to have the equal general knowledge with the public school graduates but should be better in a level of religiosity.